Profiling of the Three Circulating Monocyte Subpopulations in Human Obesity - Devêvre, Estelle F; Renovato-Martins, Mariana; Clément, Karine; Sautès-Fridman, Catherine; Cremer, Isabelle; Poitou, Christine (The Journal of immunology (1950), 2015)
Three subpopulations of circulating monocytes have been described: CD142+CD16− (classical monocytes [CM]), CD142+CD16+ (intermediate monocytes [IM]), and CD14+CD162+ (nonclassical monocytes [NCM]). We previously showed that obesity is associated with an increased proportion of IM and NCM. Our objective is to decipher the migratory and inflammatory functions of each monocyte subset in obesity-related low-grade inflammation. Twenty-six healthy, normal-weight and nondiabetic volunteers (C) and 40 obese nondiabetic (Ob) individuals were included in this study. We explored the gene expression profile of 18 inflammatory genes in each subset of C and Ob subjects and measured protein expression of the upregulated genes. We then tested their functional response to TLR signaling in both groups. We showed an increased expression of CX3CR1 in all monocyte subpopulations and of CCR2 and CCR5 in CM and IM in the Ob group. We found negative correlation between CCR2 and CX3CR1 expressions and high-density lipoprotein-cholesterol, whereas CCR5 expression was positively linked to obesity-related metabolic traits. Production of inflammatory proteins upon bacterial LPS and viral ssRNA stimulation was higher in CM and NCM of the Ob group compared with the C group. Our work highlights an enhanced inflammatory phenotype of monocytes with a higher response to TLR4 and TLR8 stimulations in obesity. Moreover, it suggests an increased migration capacity of CM and IM subpopulations.